Adsorption performance of food red 17 dye using an eco-friendly material based on luffa cylindrica and chitosan (2021)
Luffa cylindrica (LC), a lignocellulosic material coveted for its versatility, was investigated to immobilize crosslinked chitosan and remove Food red 17 (FR17) dye from aqueous solutions. LC/chitosan was crosslinked with epichlorohydrin (LC/CS/EPIC) and glutaraldehyde (LC/CS/GLUT). LC/CS/GLUT and LC/CS/EPIC presented an adequate morphology for mass transfer, relevant functional groups for adsorption. Furthermore, FR17 dye adsorption was favored at pH 2. Pseudo-second-order and Sips models represented the kinetic and isotherm data satisfactorily. The adsorption process for both adsorbents was endothermic, spontaneous, and favorable. The maximum adsorption capacity for LC/CS/GLUT was 77.66 mg g 1, and for LC/CS/EPIC was 43.01 mg g 1 for dye FR17. Furthermore, when reused, the adsorbents remain at around 70% of their original capacities after six adsorption cycles. Thus, the materials prepared from Luffa cylindrica and chitosan resulted in promising eco-friendly adsorbents.